How are Research for Development Programmes Implementing and Evaluating Equitable Partnerships to Address Power Asymmetries? - and Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) requires collaborations between partners from a range of disciplines and cultural contexts. Power asymmetries within such partnerships may obstruct the fair distribution of resources, responsibilities and benefits across all partners. This paper presents a cross-case analysis of five R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D partnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened understandings of how equitable partnerships contribute to R4D generating impact and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership principles ensured contextually appropriate definitions and a focus on what partners value.